The Role of Geogebra in Improving Students' Mathematical Representation Abilities: A Systematic Literature Review - Lutfiatussolihah Lutfiatussolihah; Aulia Aulia; Robiatul Adawiah; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of STEM Education, 2025)
This study aims to analyze the effectiveness of using GeoGebra in improving students’ mathematical representation abilities through a Systematic Literature Review (SLR) approach. The background of this study is based on the variability of findings in previous research regarding the use of GeoGebra, as well as the lack of a comprehensive synthesis examining patterns of its effectiveness in mathematics learning. The study was conducted by analyzing 15 articles selected through a screening process based on predefined inclusion and exclusion criteria, published between 2015 and 2024. The results indicate that GeoGebra generally has a positive impact on enhancing students’ mathematical representation abilities, particularly in visual, symbolic, and graphical aspects. However, its effectiveness is influenced by several factors, such as the learning model employed, student characteristics, and the suitability of the learning materials. Therefore, GeoGebra can be considered an effective tool when appropriately integrated into instructional strategies to support interactive and meaningful mathematics learning.